The Effects of Methacrylated Glucosamine on the Mechanical Properties of Gelatin Methacryloyl Hydrogels and Gelatin-Methacryloyl/Nanohydroxyapatite Composite Materials. - Tielemans, Cullen (University of Waterloo, 2021)
Gelatin-methacryloyl (GelMA) has been a material of keen research interest in the past few decades, with diverse potential applications such as drug delivery, tissue engineering, and 3D bioprinting, due to it possessing many desirable properties. However, pure GelMA hydrogel materials in published literature exhibit relatively weak mechanical properties when considering its application as a tissue-engineering material for load-bearing tissues, such as cartilage or bone. In this study, two new UV-curable additives based off the monosaccharide glucosamine were developed, with one additive being monofunctional and the other polyfunctional. These additives were explored to improve the mechanical properties of a GelMA hydrogel and a GelMA/nanohydroxyapatite composite material. Additionally, the effects of the divalent salt, CaCl2, were explored as previous research on similar materials had shown favourable interactions to lower the viscosity of uncured materials, improving handling and enabling the material to be used as a 3D printer ink. Cast hydrogel and composite materials were mechanically tested cyclically and compressively and the effects of the additives compared. Rheological properties of all materials were explored using a cup-and-bob rheometer with shear stress controlled between samples. Finally, the materials were tested on a masked stereolithography 3D printer to determine material printability. It was found that the monofunctional additive was unable to improve the mechanical properties of the hydrogel or composite materials at any tested concentration, but the polyfunctional additive improved the mechanical properties of the materials significantly, with the hydrogel being 125% tougher than the control with a 1 molar concentration. Similar improvements were observed for the composite materials. The inclusion of 100 mM CaCl2 was found to lower the viscosity of all hydrogel inks, as did the inclusion of the polyfunctional additive. The same trends were not observed for the composite material, however, as both additives increased the viscosity of the composites compared to the control, and the salt had minimal effect on the rheology of the control and polyfunctional additive composites. Both the polyfunctional additive-containing hydrogel and composite materials were found to be printable on a masked stereolithography 3D printer. The development of the polyfunctional glucosamine additive represents a step forward in the development of additives to improve the mechanical properties of biologically-derived hydrogel and composite materials, and provides insight into potential mechanisms that could be exploited in the design of future additives to drive the properties of these materials closer to the properties of load-bearing tissues while maintaining manufacturability.
Keywords: gelatin; GelMA; gelatin methacryloyl; hydrogels; glucosamine; nanohydroxyapatite; composite; mechanical properties